Meningkatkan Kinerja Guru melalui Supervisi Pembelajaran di MTs Raudhatul Islamiyah Peniti Luar Tahun 2022/2023 - Bakron, Muhammad; Susila, Rusmi (The Magister of Islamic Education IAIN Pontianak, 2023)
Professionality of educators is determined by the height or low insight of teachers about the competence of educators. Increasing competence can be done with research involving collaboration with fellow educators. This study aims to determine the effectiveness of learning supervision by madrasa leaders. Specifically the purpose of this study is to improve teacher performance through learning supervision in MTs. Raudhatul Islamiyah Peniti Outside 2022. Inui research was designed using Classroom Action Research (CAR) from the stages of research obtained the following results: In cycles I and II, the first was obtained, teacher performance increased in making learning planning. Second, teacher performance increases in carrying out learning. Third, teacher performance increases in assessing student achievement. Fourth, teacher performance increases in carrying out the follow -up to the results of student learning achievement appraisal. Fifth, teacher performance increases in developing learning programs, carrying out learning, assessing learning achievement, and carrying out follow -up of student learning achievement results. AbstrakProfesioanalitas pendidik ditentukan oleh tinggi atau rendahnya wawasan guru tentang kompetensi pendidik. Meningkatkan kompetensi dapat dilakukan dengan riset yang melibatkan kolaborasi dengan sesama pendidik. Penelitian ini bertujuan untuk mengetahui efektifitas supervisi pembelajaran oleh pimpinan madrasah. Secara spesifik tujuan dari penelitian ini adalah Peningkatan Kinerja Guru Melalui Supervisi Pembelajaran di MTs. Raudhatul Islamiyah Peniti Luar tahun 2022. Penelitian inui didesain menggunakan penelitian tindakan kelas (PTK) dari tahapan peneitian didapatkan hasil sebagai berikut: pada siklus I dan II, maka didapatkan pertama, kinerja guru meningkat dalam membuat perencanaan pembelajaran. Kedua, kinerja guru meningkat dalam melaksanakan pembelajaran. Ketiga, kinerja guru meningkat dalam menilai prestasi belajar siswa. Keempat, Kinerja guru meningkat dalam melaksanakan tindak lanjut hasil penilaian prestasi belajar peserta didik. Kelima, Kinerja guru meningkat dalam menyusun program pembelajaran, melaksanakan pembelajaran, menilai prestasi belajar, dan melaksanakan tindak lanjut hasil prestasi belajar siswa. Kata kunci : Supervisi Pembelajaran, Peningkatan Kinerja, MTs Raudhatul Islamiyah